2004
DOI: 10.1080/09637480500086141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diet quality with the mediterranean dietary quality index in university students

Abstract: Data on diet quality in Croatian university students have been missing for more than 15?years. A food approach rather than a nutrient approach appears more appropriate to present knowledge on diet and health. The aim of the present study was to evaluate diet quality in Croatian university students (n = 663) with the Mediterranean Dietary Quality Index (M-DQI) in continental and Mediterranean regions. The M-DQI was determined with a Quantified Food Frequency Questionnaire. The minimum score for the M-DQI is 0 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
4
14
0
2
Order By: Relevance
“…Consistent with the findings of others, our results showed that energy intake did not correlate with M-DQI, and correlation with macronutrients and micronutrients indicates healthful intakes for lower scores of the M-DQI (29,38) . For example, carotenoids, folic acid and vitamin C are Mean values were significantly different from those of men (one-way ANOVA) or significant r value: *P , 0?05, **P , 0?01, ***P , 0?001.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the findings of others, our results showed that energy intake did not correlate with M-DQI, and correlation with macronutrients and micronutrients indicates healthful intakes for lower scores of the M-DQI (29,38) . For example, carotenoids, folic acid and vitamin C are Mean values were significantly different from those of men (one-way ANOVA) or significant r value: *P , 0?05, **P , 0?01, ***P , 0?001.…”
Section: Discussionsupporting
confidence: 92%
“…However, such biomarkers have not been used to describe dietary patterns until recently (25,(28)(29)(30)(31)(32)(33)(34)(35)(36) . The M-DQI, applied in representative samples of the French (37) and the Croatian population (38) , has not yet been applied to a Spanish Mediterranean population.…”
mentioning
confidence: 99%
“…We do not know whether these findings can be generalized to men; however, data suggest that women tend to have healthier dietary patterns (15,20,24,27,35,36) and higher Mediterranean diet scores than do men (15,20,27,36). Furthermore, no sociodemographic or physiological information was collected for this study.…”
Section: Study Limitationsmentioning
confidence: 54%
“…The importance of nutrition knowledge in the moderation of dietary intake differs markedly between and even within individuals, depending upon the context (33). Thus, in addition to nutrition education, a number of other individual and collective factors likely influenced students' dietary patterns, including food preferences (22,34), their sex (11,15,20,21,24,27,35,36), perceived (and actual) food accessibility (22), time (37), geography (15,19), self-efficacy (22), living conditions (e.g., residing at home or away from home) (15), finances (37), and behavioural modelling (22).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation